The influence of depth on the Mediterranean reef fish assemblage revealed by the new video on underwater scooter method - Glavičić, Igor (Array, 2020)
The new video on underwater scooter method in combination with rebreather diving techniques was introduced and applied for visual census of fish assemblages. The presently applied method facilitates deeper visual census studies below 40 m, where they have rarely been done before due to the increasing research challenges with depth. The video on underwater scooter method is also expected to be less disturbing and faster compared to swimming divers. The method was applied in visual census study of fish assemblages from 8 to 50 m depth conducted at two locations in the east Adriatic using 102 video transects. The environmental variables contributing to the variation of the reef fish community in the depth range of the infralittoral and upper circalittoral bottoms were also recorded. Thirty-one fish species were recorded on transects and 10.3% of all individuals were not identified to the species level. The average density on transects was 0.8 individuals/m², with C. chromis, C. julis and G. auratus being both the most abundant and the most frequent species. Three environmental variables, depth, bottom with zoocover and eastern orientation of the coast, were identified as highly significant for species occurrence. Abundance and species richness of fish assemblages showed no significant variation with depths, inclinations, orientations and sites. A significant difference in the fish assemblage structure was found among orientations, depths and inclinations with the gradient change of species composition with increasing depth and with increasing inclination.